Seismic performance evaluation of different strategies for retrofitting RC frame buildings. (December 2021) - Zhao, Jianchen; Qiu, Hongxing; Sun, Jian; Jiang, Hongbo
Abstract: Defect RC frames are vulnerable to seismic excitation, which need to be retrofitted to enhance performance during seismic event. An applicable procedure is required to reveal the benefits and potential weakness of different retrofit strategies for RC frame buildings with different structural vibration characteristics, which are lacking in previous studies. This research investigation on evaluating the seismic performance of RC frames retrofitted with common methods, with the consideration of fundamental period varying. The seismic dynamic analysis was conducted in a simplified way for the analysis of Single Degree of Freedom (SDOF) systems with hysteresis behaviour factors calibrated on the response from the fiber finite element model of a real RC frame. The variation on the fundamental period of structures in range from 0.6 s to 2 s was considered to obtain a general result, with the consideration of five reinforcement strategies, three strength reduction factors of structures. To study the effect of peak ground acceleration, 20 real earthquake time histories and five seismic intensities were considered. The analysis results show that increasing the secondary-stiffness of the structure with dampers equipped represent an excellent effect in suppressing seismic demand of the structure. However, the strengthening by directly increasing the strength and stiffness has a potential risk of deteriorating the seismic performance of some structures under high intensity earthquakes.